Randomized clinical study comparing Piezoelectric Surgery with conventional rotatory osteotomy in mandibular third molars surgeries - Ra'ed Mohammed Ayoub Al-Delayme (Elsevier, 2021)
Purpose: The aim of this study was to evaluate the performance and to assess the postoperative sequel and quality of life after removal of impacted mandibular third molars using piezoelectric surgery compared with conventional rotatory osteotomy. Patients and methods: A single blinded, randomized, control clinical study was performed. Sixty-three patients (44 males, 19 females) who presented with bilaterally asymptomatic impacted mandibular third molars were included in this analysis. Each patient was treated, at two separate sessions approximately 4 weeks apart, with a conventional rotatory hand piece on one side of the mandible and a piezoelectric device on the contralateral side. Patients were followed up on postoperative days 1, 3, 5, 7, and 15 to rate the pain, swelling and trismus. Inferior alveolar nerve paresthesia was evaluated up to 12 months postoperatively. Results: The severity of the pain, trismus and swelling using the piezosurgery were significantly different from the rotary group. In both groups, pain was most intense and peaked during the first post-operative day, while swelling and trismus reached peak levels on the third postoperative day. The piezoelectric procedure resulted in a significantly longer procedural duration compared to the rotatory surgery (P < 0.001). Conclusion: Piezoelectric surgery is considered a viable alternative technique compared to the conventional rotary systems and can improve a patient's quality of life. Thus, piezoelectric surgery might be a preferred modality for patients undergoing complicated surgical extraction of impacted lower third molars.